Anterior Cervical Corpectomy and Fusion with excision of recurrent long segmental midline anterior cervical arachnoid cyst - Thapa, Ashish Jung; Tandon, Asheesh; Agrawal, Alok (Nepal Journal of Neuroscience, 2020)
Anterior midline cervical arachnoid cysts are very rare, common in the thoracic region. The treatment of midline ventrally lying arachnoid cyst may be challenging via a posterior approach because of a lack of direct visualization of the entire cyst, in particular, its attachment to the cord, complete excision of the cyst wall through a posterior approach is not always possible. Incomplete excision at the first operation and the reaction caused by the epithelial secretion from the marsupialized cyst makes surgery for recurrence very difficult. So, Anterior cervical corpectomy and fusion (ACCF) with cyst excision may be the ideal approach for the anterior midline arachnoid cyst with complete removal and fewer chances of recurrence. Here we report a case of long segmental recurrent midline anterior arachnoid cyst which is completely excised using an anterior cervical corpectomy and fusion and the patient improved drastically neurologically.